Kinetics and Mechanism of Oxidation of 6-[2-Amino-2-(4-hydroxyphenyl)acetylamino]-3,3-dimethyl-7-oxo-4-thiol-1-azabicyclo[3,2,0]heptane-2-carboxylic acid (Amoxicillin Trihydrate) with Bi(V) in HClO4-HCl Mixture - Mishra, Parashuram (Asian Journal of Chemistry, 2010)
Kinetics of oxidation of amoxicillin with Bi(V) complex has been studied in HClO4-HCl mixture. The stoichiometry of Bi(V) with amoxicillin in acidic medium was established in the pH range 2.0-3.0 by iodometric and spectrophotometric methods. The oxidation follows first order kinetics in Bi(V) with [AX] is unity and increases the rate. Oxidation products have been proposed. Dependence of reaction rate on temperature has been studied and Eyring's activation parameters were computed. The mode of electron transfer from the substrate to the oxidant has been explained on the basis of bridged outer sphere mechanisms.